Lime effect on Sisyrinchium platense Johnst (Iridaceae) control - Macedo, Walfredo; Girardi-Deiro, Ana Maria; da Mota, Adilson Ferreira (Pesquisa Agropecuaria Brasileira, 1995)
Sisyrinchium platense is a plant occurring on natural pasture at the southwestern region of Rio Grande do Sul, Brazil, on a Brunizen Vertic and non Vertic soil of granitic origin and medium fertility. Aiming at the establishment of the effect of the dolomitic lime in controlling this plant, an experiment was carried out into a glasshouse during 180 days. The treatments were four levels of dolomitic lime (0 - 4.5 - 9.0 -13.5 ton/ha) applied at the soil surface or mixed with the soil surface layer in a randomized complete block design with four replicates. The results showed no lime effect on controlling the stand of Sisyrinchium plants, when applied on the soil surface. When lime was mixed in the 15 cm deep of the soil surface layer, at levels of 4.5 - 9.0 and 13.5 ton/ha, it decreased plants vigour and height and also avoided the flowering and seed production.